Simultaneous determination of chlorite, chlorate, perchlorate and bromate in ozonated saline by using IC-MS. Issue 48 (8th December 2020) - Yin, Xiuzhen; Cui, He; Li, Sa; Niu, Shuyan
Abstract : A simple, accurate and reliable analytical method for simultaneous determination of chlorite, chlorate, perchlorate and bromate in ozonated saline by using ion chromatography coupled with triple quadrupole mass spectrometry (IC-MS) has been developed. Abstract : A simple, accurate and reliable analytical method for simultaneous determination of chlorite, chlorate, perchlorate and bromate in ozonated saline by using ion chromatography coupled with triple quadrupole mass spectrometry (IC-MS) has been developed. The use of silver (Ag) and hydrogen (H) OnGuard cartridges and 100-fold dilution were found to be simple and effective for sample pretreatment. Under optimized MS parameters, method validation was convincingly confirmed. A good linearity was obtained with regression correlation coefficients ( R 2 ) larger than 0.999. The mean relative recoveries of chlorite (ClO2 − ), chlorate (ClO3 − ), perchlorate (ClO4 − ), and bromate (BrO3 − ) ranged from 79.96 to 97.63%. The obtained limit of detection (LOD) was 1.00 μg L −1 for ClO2 −, 0.10 μg L −1 for ClO3 −, 0.04 μg L −1 for ClO4 −, and 0.50 μg L −1 for BrO3 − . Chlorate and bromate were only detected in ozonated samples. In addition, the concentration of chlorate and bromate was in direct proportion to the amount of ozone in saline.